1998
DOI: 10.1046/j.1365-2958.1998.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Schizosaccharomyces pombe isp4 encodes a transporter representing a novel family of oligopeptide transporters

Abstract: SummaryWe have recently cloned an oligopeptide transport gene from Candida albicans denoted OPT1. This gene showed significant sequence similarity to three open reading frames (ORFs) with no previously established function: isp4 from Schizosaccharomyces pombe and Saccharomyces cerevisiae YJL212C and YPR194C, identified during the genome project. The S. pombe gene isp4 was originally identified by Sato et al. as a gene that was upregulated through nitrogen starvation induction of meiosis. However, an isp4⌬ stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(95 citation statements)
references
References 47 publications
(78 reference statements)
4
91
0
Order By: Relevance
“…3B). As reported previously by Lubkowitz et al (1998), none of the OPT family members showed any significant sequence similarity to the known ABC or PTR peptide transporters (data not shown).…”
Section: Molecular Characterization Of Osopt10 Proteinsupporting
confidence: 82%
See 1 more Smart Citation
“…3B). As reported previously by Lubkowitz et al (1998), none of the OPT family members showed any significant sequence similarity to the known ABC or PTR peptide transporters (data not shown).…”
Section: Molecular Characterization Of Osopt10 Proteinsupporting
confidence: 82%
“…In contrast to PTR peptide transporters, the yeast OPT transporters predominantly recognize tetra-and pentapeptides (Lubkowitz et al 1997;Lubkowitz et al 1998), including the endogenous opioids Met-enkephalin (YG GFM) and Leu-enkephalin (YGGFL) (Hauser et al 2000). Database searches for homology with the C. albicans CaOpt1p revealed nine putative Arabidopsis OPT orthologs that form a distinct subfamily compared with the fungal OPTs Stacey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that Arabidopsis homologues of YS1, the 8-member YSL (YS-like) family, may be involved in transporting NA-metal chelates within the plant (60). OPT and YSL are two divergent families of proteins (63) with homology to ISP4, a fungal oligopeptide transporter (64). Our yeast complementation experiments have shown that AtOPT3 can transport copper, manganese, and possibly iron as it was suggested by the transcriptional regulation pattern.…”
Section: Independent Systems Of Copper and Iron Homeostasis In Arabidmentioning
confidence: 60%
“…Furthermore, Gln-222 was found conserved among different OPT members, whereas Gln-526 was present only in Pgt1 but not in the other functionally characterized oligopeptide transporters. This differential pattern of conservation and effect of mutations of Gln-222 and Gln-526 becomes particularly remarkable as Pgt1, like Hgt1p, is the only other PT member characterized to transport glutathione with high affinity, whereas all the other three PT members, AtOpt4, CaOpt1, and Isp4, have been shown to transport tetrapeptides and pentapeptides but do not transport glutathione (4,7,35,36). Taken together, the results suggest that although both glutamine residues participate in substrate transport, Gln-526 is critical in identifying glutathione as substrate, whereas Gln-222 recognizes a structural feature common to oligopeptides, including glutathione, a modified tripeptide.…”
Section: Discussionmentioning
confidence: 99%
“…These include Pgt1, CaOpt1, Isp4, and AtOpt4. Pgt1 has been recently characterized as a high affinity glutathione transporter from Schizosaccharomyces pombe (4), whereas AtOpt4 from Arabidopsis thaliana, CaOpt1 from Candida albicans, and Isp4 from S. pombe have been shown to specifically mediate uptake of oligopeptides (7,35,36).…”
Section: Conservation Pattern Of Residues Important For Hgt1p Functiomentioning
confidence: 99%